Pengaruh Pemberian Edukasi Informed Consent Persiapan Operasi Terhadap Tingkat Kecemasan Pasien Pra Operasi SC di RSIA Murni Teguh Medan - Dewi Lestari Nababan; Harsudianto Silaen (Corona: Jurnal Ilmu Kesehatan Umum, Psikolog, Keperawatan dan Kebidanan, 2025)
Background: Sectio caesarea is performed to ensure the safety of the mother and baby. Before the operation, health workers, especially nurses, need to provide education to the mother about informed consent and the operation procedure to reduce the mother's anxiety and concerns about the safety of her baby. Objective: To determine the effect of providing informed consent education on surgical preparation with anxiety levels in patients with Pre-Operational Caesarean Section. Method: This study is an analytical survey study using the cross-sectional method. The study was conducted at RSIA Murni Teguh Rosiva Medan. The population was 30 people and all of them were used as samples, sampling was done using purposive sampling. The analysis was performed univariately in the frequency distribution table and bivariately using the Kendall's tau-b test. Results: This study showed that the majority of pre-operative caesarean section patients stated that the provision of informed consent education in preparation for surgery was in the good category (60.0%). The majority of pre-operative caesarean section patients felt mild anxiety (50.0%). The provision of informed consent education in preparation for surgery had a significant effect on the level of anxiety of pre-operative caesarean section patients at RSIA Murni Teguh Rosiva Medan, p-value = 0.005 <0.05. Conclusion: The anxiety of pre-operative caesarean section patients was influenced by the provision of informed consent education in preparation for surgery by nurses. Suggestion: It is recommended that nurses provide informed consent education regarding preparation for caesarean section surgery to improve the knowledge and readiness of mothers to overcome anxiety that can affect caesarean section procedures.